Ni3S2 nanowires grown on nickel foam as an efficient bifunctional electrocatalyst for water splitting with greatly practical prospects. (16th April 2018) - Zhang, Dawei; Li, Jingwei; Luo, Jiaxian; Xu, Peiman; Wei, Licheng; Zhou, Dan; Xu, Weiming; Yuan, Dingsheng
Abstract: It is essential to synthesize low-cost, earth-abundant bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reactions (OER) for water electrolysis. Herein, we present a one-step sulfurization method to fabricate Ni3 S2 nanowires directly grown on Ni foam (Ni3 S2 NWs/Ni) as such an electrocatalyst. This synthetic strategy has several advantages including facile preparation, low cost and can even be expanded to large-scale preparation for practical applications. The as-synthesized Ni3 S2 NWs/Ni exhibits a low overpotential of 81 and 317 mV to render a current density of 10 mA cm −2 for the HER and OER, respectively, in 1.0 mol l −1 KOH solution. The Ni3 S2 NWs/Ni was integrated to be the cathode and the anode in the alkaline electrolyzer for overall water splitting with a current density of 10 mA cm −2 afforded at a cell voltage of 1.63 V. More importantly, this electrolyzer maintained its electrocatalytic activity even after continual water splitting for 30 h. Owing to its simple synthesis process, the earth-abundant electrocatalyst and high performance, this versatile Ni3 S2 NWs/Ni electrode will become a promising electrocatalyst for water splitting.